1983
DOI: 10.1073/pnas.80.3.797
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian mutator mutant with an aphidicolin-resistant DNA polymerase alpha.

Abstract: The Chinese hamster V79 cell mutant aphr4-2, selected for its resistance to aphidicolin, a specific inhibitor of DNA polymerase a (DNA nucleotidyltransferase, EC 2.7.7.7), is characterized by slow growth, UV sensitivity, and hypersensitivity to UV-induced mutation. DNA polymerase a has been purified from mitochondria-free crude extracts of the mutant and its parental wild-type cells by sequential column chromatography on DEAE-cellulose and phosphocellulose. The major DNA polymerase activity from both cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
1

Year Published

1983
1983
2004
2004

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 42 publications
1
18
1
Order By: Relevance
“…None of the cell clones had any alteration in sensitivity to these agents. The results suggested that these mutator mutants were different from the mutator mutants reported by Liu et al (9), which showed hypersensitivity to UV.…”
Section: And Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…None of the cell clones had any alteration in sensitivity to these agents. The results suggested that these mutator mutants were different from the mutator mutants reported by Liu et al (9), which showed hypersensitivity to UV.…”
Section: And Discussioncontrasting
confidence: 54%
“…These cell clones were first isolated as mutants with altered sensitivity to inhibitors of DNA replication, such as arabinofuranosylcytosine (AraC) or aphidicolin. In addition to these mutator mutants, Liu et al (9) recently reported that one of the mutants resistant to aphidicolin had altered DNA polymerase a. They showed that the mutant DNA polymerase was resistant to aphidicolin and had a decreased Km for dCTP.…”
mentioning
confidence: 99%
“…At this point, the reaction products were chased with a 300-fold excess of cold dCTP followed immediately by various amounts of aphidicolin. (Aphidicolin is an inhibitor of human pol alpha, delta, and epsilon, whose presence leads to chain termination [13,16]. In an Ad-infected extract, the presence of 0.25, 0.5, and 1.0 M aphidicolin inhibits total AAV DNA replication by 68, 83, and 93%, respectively [data not shown].)…”
Section: Resultsmentioning
confidence: 99%
“…Abnormalities in DNA repair and replication have also long been considered as key elements in the genesis of mutations. Several mechanisms can be invoked to contribute to the infidelity of DNA synthesis, including imbalances in deoxynucleotide triphosphate pools, mutations in DNA polymerase-a and slippage of DNA polymerase at nucleotide repeats (Liu et al, 1983;Phear et al, 1987;Kunkel et al, 1993). However, the importance of each mechanism and gene(s) involved is often unknown.…”
Section: Silencing Of Mgmt Causes a New Mutator Pathway In Human Cancermentioning
confidence: 99%